Later high school start time is associated with lower migraine frequency in adolescents. Issue 2 (25th November 2020) - Gelfand, Amy A.; Pavitt, Sara; Ross, Alexandra C.; Szperka, Christina L.; Irwin, Samantha L.; Bertisch, Suzanne; Stone, Katie L.; Frazier, Remi; Grimes, Barbara; Allen, I. Elaine
Abstract: Objective: To determine whether high school start time is associated with headache frequency in adolescents with migraine. Background: Adolescence is marked by a physiologic delayed circadian phase, characterized by later bedtimes and wake times. The American Academy of Pediatrics (AAP) recommends that high schools start no earlier than 8:30 a.m., but most high schools in the United States start earlier. The study hypothesis was that adolescents with migraine whose high schools start at 8:30 a.m. or later (late group) would have lower headache frequency than those whose schools start earlier than 8:30 a.m. (early group). Methods: This was a cross‐sectional Internet survey study of US high schoolers with migraine recruited online through social media. Comparisons were made between the late group and the early group. The primary outcome measure was self‐reported headache days/month. Results: In total, 1012 respondents constituted the analytic set: n  = 503 in the late group versus n  = 509 in the early group. Mean (SD) self‐reported headache days/month was 4.8 (4.6) versus 7.7 (6.1) in the late and early groups, respectively ( p  < 0.001); mean difference −2.9 (95% CI −2.2 to −3.6). Mean (SD) self‐reported hours of sleep on a school night was 7.9 (0.9) versus 6.9 (1.3), p  < 0.001. Adjusting for total hours of sleep, sex, taking a migraine preventive, days of acute medication use, hours of homework, grade level, and missing breakfast, mean (SD) self‐reported headache days/month remained lower in the late group than in the early group: 5.8 (95% CI 5.3–6.2) versus 7.1 (95% CI 6.7–7.4), ( p  < 0.001); mean difference −1.3 (95% CI −1.9 to −0.7). Conclusion: Adolescents with migraine who attend high schools that follow AAP recommendations for start times have lower self‐reported headache frequency than those whose high schools start before 8:30 a.m. If prospective studies confirm this finding, shifting to a later high school start time may be an effective strategy for migraine prevention in adolescents.